Flameless venting of dust explosion: Testing and modeling. (November 2021) - Grégoire, Yann; Leprette, Emmanuel; Proust, Christophe
Abstract: Flameless venting is a sort of dual mitigation technique allowing, in principle, to vent a process vessel inside a building where people are working without transmitting a flame outside the protected vessel. Existing devices are an assembly of a vent panel and a metal filter so that the exploding cloud and the flame front is forced to go through the filter. Within the frame of ATEX Directive, those systems need to be certified. To do so a standard (NF EN 16009) has been issued describing which criteria need to be verified/measured. Among them, the "efficiency" factor as defined earlier for standard vents. This implies that flameless venting systems are basically considered as vents. But is it really so? This question is discussed on the basis of experimental results and some implications on the practical use and certification process are drawn. The practical experience of INERIS in testing such systems is presented in this paper. Schematically, with a flameless vent the pressure is discharged but not the flame so that combustion is proceeding to a much longer extent inside the vessel than with a classical vent so that the physics of the explosion is different. In particular it is shown that besides the problem of the unloading of the confined explosion, there is a highly complicated fluid mechanics problem of a fluid-particle flow passing through a porous media (the flameless device grids arrangement in the filter), which passing surface is progressively reduced. To characterize Flameless venting the problem can be addressed sequentially, considering separately the vent panel and the flameless mesh. A model is proposed to estimate the overall venting efficiency of the flameless vent. However, it does not address the flame quenching issue, which is a different problem of heat exchange between the devices and the evacuated burnt products. Highlights: Flameless vents behave as vents, as assumed by EN16009, only in specific conditions. Recommandations for testing in the scope of certification are proposed. Flameless venting implies two problems: venting and flame quenching. Dust morphology and concentration affects the venting efficiency. A model for Flameless vent efficiency calculation is proposed.